The association between Diet Quality Index–International score and risk of diminished ovarian reserve: a case–control study - Ziaei, Rahele; Ghasemi-Tehrani, Hatav; Movahedi, Minoo; Kalatehjari, Maryam; Vajdi, Mahdi; Mokari-Yamchi, Amin; Elyasi, Mahshid; Ghavami, Abed (Frontiers in Nutrition, 2023)
Although limited evidence exists on the beneficial reproductive effects of diet quality indices, the association is still largely unknown. We aimed to investigate the association between diet quality index-International (DQI-I) and antral follicle count (AFC) and serum antimullerian hormone (AMH), as precise and sensitive markers of ovarian reserve, and risk of diminished ovarian reserve (DOR) in women seeking fertility treatments. In a case-control study, 370 women (120 women with DOR and 250 women with normal ovarian reserve as controls), matched by age and BMI, were recruited. Dietary intake was obtained using a validated 80-item semi-quantitative food frequency questionnaire (FFQ). The quality of diets was assessed using DQI-I, which included four major dietary components including variety (0-20) points, adequacy (0-40), moderation (0-30), and overall balance (0-10). DQI-I score was categorized by quartiles based on the distribution of controls. Antral follicle count (AFC), serum antimullerian hormone (AMH) and anthropometric indices were measured. Logistic regression models were used to estimate multivariable odds ratio (OR) of DOR across quartiles of DQI-I score. Increased adherence to DQI-I was associated with higher AFC in women with DOR. After adjusting for potential confounders, the odds of DOR decreased with increasing DQI-I score (0.39; 95%CI: 0.18-0.86). Greater adherence to DQI-I, as a food and nutrient-based quality index, may decrease the risk of DOR and improve the ovarian reserve in women already diagnosed with DOR. Our findings have to be verified in prospective studies and clinical trials.